Diversidade cromossômica no gênero Micrathena Sundevall, 1833 (Araneae, Araneidae) - CAROLINE CORREIA DA COSTA (2022)
Spiders constitute a megadiverse group, currently with 50,224 taxonomically described species, divided into 132 families, with hundreds of new descriptions each year. Despite the enormous diversity, only 849 species of spiders have been studied from a chromosomal point of view, which represents only 1.7% of all taxonomically known species. The diploid number varies from 2n♂ = 5, in Afrilobus sp. (Orsolobidae), to 2n♂ = 152 in Caponia natalensis (O. Pickard-Cambridge, 1874), the predominant chromosomal morphology is acro/telocentric and the most common sex chromosome system (SCS) is of the type X1X2 in males and X1X1X2X2 in females. Cytogenetics provides data such as diploid number, chromosome morphology, SCS type, behaviour of chromosomes in meiosis, distribution pattern of specific chromatin regions, among others, which can be used in the comparison between species.